Identification and Validation of Entrustable Professional Activities in Indonesian Internal Medicine Residency Programs - Ikhwan Rinaldi; Ardi Findyartini; Sandra Widaty; Irsan Hasan (Interna Publishing, 2022)
Background: Entrustable professional activities (EPAs) are tasks entrusted to students who assist supervisors in determining their competencies. However, the competencies required and the end-educational stage in which each EPA item is assigned have yet to be determined by the stakeholders of internal medicine residency programs in Indonesia. This study aimed to identify and determine the activities in internal medicine residency programs which could be defined as EPAs in the competency-based curriculum of Indonesian internal medicine residency programs. Methods: A literature review was conducted to identify activities which could be examined as EPA items in Indonesian internal medicine residency programs, which were then validated by 10 educational experts. Two rounds of the Delphi method were conducted with participants consisting of the Indonesian Board of Internal Medicine professionals, residency program directors, internal medicine specialists, and internal medicine residents to evaluate the importance of the identified EPA items. The EPA items were rated on a Likert scale ranging from 1 to 5, and their variances were analyzed. The participants also rated the end-educational stage appropriate for each EPA item. The effect size was calculated between groups as (1) small, <0.3; (2) moderate, approximately 0.5; and (3) large, >0.8. Results: The literature review identified 29 modified items from the Royal College of Physicians and Surgeons (RCPS) and three items from other academically developed EPA designs. The expert discussion resulted in the validation of 28 EPA items (out of the 32 items in the initial EPA draft). All 28 items were accepted after two rounds of the Delphi method, and a decrease in their variances was found. Conclusion: This study formulated 28 EPA items for Indonesian internal medicine residency programs. Further collaboration between the Board of Internal Medicine and residency program directors will be needed for the application of these EPA items at each residency year.